Longitudinal Changes in Vocational Interests of Canadian MilitaryCollegeCadets - Navran, Leslie; Walker, Robert W. (Canadian Journal of Counselling and Psychotherapy, 2012)
Interest patterns of Canadian military college cadets were acquired by administering the Strong Vocational Interest Blank to three consecutive entry classes (N = 400) at the beginning, middle and end of their 4-year baccalaureate programs. Complete data were gathered on 136 of the 168 cadets who graduated. Significant changes occurred on 16 of 22 Basic Interest Scales, 38 of 54 Occupational Scales, and 4 of 8 Non-Occupational Scales. The bulk of these changes were accomplished in the first two years. They reflected the cadets' movement from an initially masculine position rooted in the physical sciences and technical and skilled trades to a more aesthetic-cultural, articulate and humanistic orientation. This was accompanied by increased dispersion and heterogeneity on all but one of the SVIB scales.